Precautionary Demand for Foreign Assets in Sudden Stop Economies : An Assessment of the New Merchantilism - Mendoza, Enrique (IMF Working Papers; Working Paper ;, 2007)
Financial globalization was off to a rocky start in emerging economies hit by Sudden Stops in the 1990s. The surge in foreign reserves since then is viewed as a New Merchantilism in which reserves are a war-chest for defense against Sudden Stops. We conduct a quantitative assessment of this argument using a framework in which precautionary savings affect foreign assets via business cycle volatility, financial globalization, and endogenous Sudden Stops. Our results show that financial globalization and Sudden Stop risk are plausible explanations of the surge in reserves but cyclical volatility, which has declined in the globalization period, is not.